The Narrow Road to the Western Isles — If Keats had journeyed with Bashō. (April 2014) - W, G
Abstract : The Japanese poet we know by the pen name Bashō was born in 1644 in Iga Ueno, a castle town in an old province south-east of Kyōto. By an almost perfectly tidy coincidence, he died one hundred and one years before John Keats was born in London in 1795. Although to all appearances their worlds and their lives could not have been more different, their poetic sensibilities seem to have been strikingly similar. This is not an original observation: it was, for instance, at the heart of an essay by James Kirkup in The Keats-Shelley Review in 1996 (vol. 10, pp. 65–75). But in what follows I try to give the observation a new twist by likening Keats and Bashō as travellers — travellers, that is, both in the literal and the metaphorical sense.